Pengaruh Kompetensi Dan Promosi Jabatan Terhadap Kinerja Personel Polri Pada Satuan Samapta Polres Sampang - Chamariyah Chamariyah; Joko Dwi Agus; Wasis Budiarto (Universitas 45 Surabaya, 2024)
The results of the study show that: 1) Competence has a positive and insignificant effect on performance as evidenced by the original sample value of 0.131 and the p-value of 0.246. 2) Promotion has a significant positive effect on performance as evidenced by the original sample value of 0.561 and the p-value of 0.000.